Solar parks provide heterogeneous habitats for winter‐active ground‐dwelling predatory arthropods - Hamřík Tomáš; Szabó Márton Zoltán; Gallé‐Szpisjak Nikolett; Michalko Radek; Tölgyesi Csaba; Torma Attila; Gallé Róbert (2026)
Winter‐active ground‐dwelling spiders and ground beetles mainly inhabit non‐crop habitats (e.g., grasslands and forests) with complex‐structured vegetation and stable microclimates. In spring, they migrate from non‐crop habitats into crop fields, contributing to pest control. Nowadays, there is an increasing number of solar parks in agricultural landscapes. However, the role of solar parks as habitats for winter‐active ground‐dwelling spiders and ground beetles and thus their potential contribution to pest control has not been studied yet. We investigated how different habitat types (i.e., forest, grassland, habitat between and under solar panels and abandoned farmland) are associated with variation in microclimatic conditions (i.e., air temperature and humidity) and with the diversity of winter‐active ground‐dwelling spiders and ground beetles across 50 sites in western Hungary. Using pitfall traps, we collected 957 ground‐dwelling spiders belonging to 69 species and 327 ground beetles belonging to 40 species. We recorded microclimatic conditions using data loggers simultaneously with arthropod sampling. We showed that patterns in arthropod assemblages likely reflect differences in microclimatic conditions across habitat types. Solar parks hosted species of different habitats (e.g., forest, grassland, wetland) with a relatively strong preference for humidity. Solar parks also supported a high abundance of agrobiont ground‐dwelling spiders (i.e., species dominant in agroecosystems). In contrast, grasslands and abandoned farmlands exhibited the most extreme microclimatic conditions, supporting mainly dry‐habitat species. Our results demonstrate for the first time that solar parks can serve heterogeneous habitats for diverse assemblages of winter‐active ground‐dwelling spiders and ground beetles and may positively contribute to biocontrol and biodiversity conservation.
Keywords: Biológiai tudományok